Polymerization of C9 enhances bacterial cell envelope damage and killing by membrane attack complex pores - Dennis J. Doorduijn (Public Library of Science (PLoS), 2021)
Complement proteins can form membrane attack complex (MAC) pores that directly kill Gram-negative bacteria. MAC pores assemble by stepwise binding of C5b, C6, C7, C8 and finally C9, which can polymerize into a transmembrane ring of up to 18 C9 monomers. It is still unclear if the assembly of a polymeric-C9 ring is necessary to sufficiently damage the bacterial cell envelope to kill bacteria. In this paper, polymerization of C9 was prevented without affecting binding of C9 to C5b-8, by locking the first transmembrane helix domain of C9. Using this system, we show that polymerization of C9 strongly enhanced damage to both the bacterial outer and inner membrane, resulting in more rapid killing of several Escherichia coli and Klebsiella strains in serum. By comparing binding of wildtype and ‘locked’ C9 by flow cytometry, we also show that polymerization of C9 is impaired when the amount of available C9 per C5b-8 is limited. This suggests that an excess of C9 is required to efficiently form polymeric-C9. Finally, we show that polymerization of C9 was impaired on complement-resistant E. coli strains that survive killing by MAC pores. This suggests that these bacteria can specifically block polymerization of C9. All tested complement-resistant E. coli expressed LPS O-antigen (O-Ag), compared to only one out of four complement-sensitive E. coli. By restoring O-Ag expression in an O-Ag negative strain, we show that the O-Ag impairs polymerization of C9 and results in complement-resistance. Altogether, these insights are important to understand how MAC pores kill bacteria and how bacterial pathogens can resist MAC-dependent killing. Author summary In this paper, we focus on how complement proteins, an essential part of the immune system, kill Gram-negative bacteria via so-called membrane attack complex (MAC) pores. The MAC is a large pore that consists of five different proteins. The final component, C9, assembles a ring of up to 18 C9 molecules that damages the bacterial cell envelope. Here, we aimed to better understand if this polymeric-C9 ring is necessary to kill bacteria and if bacteria can interfere in its assembly. We uncover that polymerization of C9 increased the damage to the entire bacterial cell envelope, which resulted in more rapid killing of several Gram-negative species. We also show that some clinical Escherichia coli strains can block polymerization of C9 and survive MAC-dependent killing by modifying sugars in the bacterial cell envelope, namely the O-antigen of lipopolysaccharide. These insights help us to better understand how the immune system kills bacteria and how pathogenic bacteria can survive killing.